A Hexagonal (II) Phase Phospholipid Neutralization Assay for Lupus Anticoagulant Identification - Triplett, Douglas A; Barna, Linda K; Unger, Gail A (Thrombosis and Haemostasis, 1993)
Lupus anticoagulants (LAs) are immunoglobulins (IgG, IgM, or both) which interfere with in vitro phospholipid (PL) dependent tests of coagulation (e.g. APTT, dilute PT, dilute Russell Viper Venom Time). These antibodies may be identified in a wide variety of clinical settings. With the exception of heparinized patient samples, the presence of LAs is often the most common cause of an unexplained APTT in a routine clinical laboratory. The diagnosis of LAs is difficult due to variable screening reagent sensitivity and intrinsic heterogeneity of LAs. Recently, Rauch and colleagues have shown human monoclonal hybridoma LAs were inhibited by hexagonal (II) phase PLs. In contrast, lamellar phase PLs had no effect. We have evaluated a new assay system, Staclot LA®, which utilizes a hexagonal (II) phase PL (egg phosphatidylethanolamine [EPE]) as a confirmatory test for LAs. Plasma samples from the following patient populations were studied: LA positive, heparinized, oral anticoagulated, hemophilia A and B, and specific factor inhibitors (factors V, VIII, IX). Unlike previous studies, the LA positive patients were a mixed population including: autoimmune diseases, drug-induced, and post-infection. Our findings confirm the specificity of hexagonal (II) phase PL neutralization of LAs.